Public Relations Practitioners' Attitudes Toward the Utilization of Artificial Intelligence Technologies in the Tourism Sector (The International Journal of Educational Sciences and Arts, 2025)
This study explores public relations practitioners' attitudes toward the use of artificial intelligence (AI) technologies in the tourism sector. It examines their understanding, application, and the challenges they face. Using a descriptive methodology, data were collected via a survey distributed to a purposive sample of 200 practitioners across various tourism institutions. Results indicate that most practitioners utilize AI in data analysis, customer service, and promotional campaigns. Key benefits include enhanced customer experience, increased efficiency, and improved competitive advantage. However, challenges such as lack of training, high costs, and privacy concerns were also identified. The study recommends adopting comprehensive training programs and investing in digital infrastructure to maximize AI integration in tourism public relations practices.
Keywords: Public Relations Practitioner; Artificial Intelligence Technologies; Tourism Sector